Accessing small business support programmes in Maseru, Lesotho - Monese, Azael Limpho (University of the Free State, 2022)
The terms small and medium enterprise (SME) and entrepreneurship were developed in the late 1940s. In developing these terms, policies emerged that included grants, subsidised credits, and special taxes for SMEs. It also included the establishment of small business support agencies funded by governments for the benefit of SMEs. The agencies were established in Japan, the United States of America (USA), India, Tanzania and Turkey in 1948, 1953, 1954, 1966, and 1976, respectively (Keskin et al., 2010, p. 189). According to the Organisation for Economic Cooperation and Development (OECD), SMEs are essential participants in the economy and the broader business ecosystem (OECD, 2022, p. 19). SMEs play a critical role in achieving the Sustainable Development Goals (SDGs) by promoting inclusive and sustainable economic growth, providing employment and decent work for all, promoting sustainable industrialisation and fostering innovation, and reducing income inequalities across countries at all stages of development (OECD, 2017, p. 8). In 2016, the government of Lesotho developed the Micro, Small, and Medium Enterprises (MSME) policy, aiming to address the issues and problems affecting the development of MSME in Lesotho (Masupha, Beharry-Ramraj and Amolo, 2017, p. 7). The policy identified challenges to MSMEs as access to finance, market access, technological development and innovation, entrepreneurial training, skills development, infrastructural development, and business working space (Molebatsi, 2021, p. 20). Therefore, this study aimed to evaluate the small business support programmes in Maseru, Lesotho, by establishing the types of small business support programmes available, determining the barriers for small businesses to access the SMEs support programmes, and lastly, determining what needs to be done to improve existing small business support programmes to ensure that they address SME challenges.
Dissertation (MBA (Business Administration))--University of the Free State, 2022